Emerging specializations, competences and firms' proximity in digital industries: The case of London. Issue 2 (8th May 2018) - Losurdo, Francesco; Marra, Alessandro; Cassetta, Ernesto; Monarca, Umberto; Dileo, Ivano; Carlei, Vittorio
Abstract: In order to overcome the limitations of defining industrial specializations in digital industries through SIC codes, this paper suggests measuring the specializations and competences of these industries on the basis of the degree of digital technologies present in the products and services supplied. Metadata from CrunchBase are employed, as proxies of firms' specializations and competences which are defined as the fields of activity in which firms are involved. Applying a network analysis, these specializations and competences are linked to the recognition of emerging digital technologies and the strongest combinations of products and services. We tested the proposed methodology on London, a leading centre for the digital economy.